Design of low‐Pb high‐piezoelectric materials via morphotropic phase boundary approach. (14th August 2022) - Zhou, Chao; Zhang, Xiaoxiao; Wang, Jieqiong; Yu, Tiantian; Gao, Jinghan; Liu, Wenfeng; Zhang, Yin; Tian, Fanghua; Shen, Yijun; Yang, Sen
Summary: Piezoelectric materials can realize the energy conversion between electrical energy and mechanical energy, thus being the key materials for energy generation and harvesting devices. According to the chemical compositions, piezoelectric materials are divided into two types: Pb‐free and Pb‐based ones. Considering the piezoelectricity, thermal stability and feasibility of large‐scale fabrication, Pb‐based piezoelectric materials cannot be substituted by Pb‐free materials at present, despite that the former are facing global restrictions because of the toxicity of Pb. In this work, a compromise strategy is proposed to design piezoelectric materials with low Pb content, through producing the morphotropic phase boundary (MPB) in the pseudo‐binary system, with one end member being Pb‐free compound Ba(Ti0.8 Zr0.2 )O3 and the other one being Pb‐doped compound (Ba0.8 Pb0.2 )TiO3 . Then large piezoelectricity is expected at MPB due to the peculiar thermodynamic feature—two‐phase coexistence and low energy barrier. The phase diagram of (1− x )Ba(Ti0.8 Zr0.2 )O3 ‐ x (Ba0.8 Pb0.2 )TiO3 consists of cubic, rhombohedral, and tetragonal phases, which is constructed based on the dielectric permittivity vs temperature curves and the X‐ray diffraction profiles. At room temperature, the optimum composition x  = 0.5 that locates around MPB, exhibits the highest piezoelectricity ( d 33  ~ 360 pC/N) and can compete with conventional Pb‐based piezoelectric materials, that is, Pb(Zr1−x Tix )O3, but contains much lower content of Pb. Our work provides an efficient strategy to design low Pb content materials with large piezoelectricity, and such strategy may be the optimum solution presently that satisfies both the device performance requirement and the more rigorous approval for use of Pb. Abstract : Through the route of constructing the morphotropic phase boundary (MPB), a new low‐Pb content piezoelectric system, (1− x )Ba(Zr0.2 Ti0.8 )O3 − x (Ba0.8 Pb0.2 )TiO3, was designed and fabricated. The optimum composition x  = 0.5 that locates around MPB exhibits the highest piezoelectricity ( d 33  ~ 360 pC/N) and can compete with Pb‐rich piezoelectric materials. Our work provides an efficient method to design low‐Pb content materials with large piezoelectricity.